THE IMPORTANCE OF LIGHTING IN ARCHITECTURAL WORK ENVIRONMENT PROJECTS - de Oliveira Rodrigues, Mirela; de Oliveira Scalise, Walnyce (Journal of Interdisciplinary Debates, 2022)
The purpose of this research is to understand what lighting is, the types of lighting and lamps available on the market, which factors and technical parameters should be considered to obtain adequate lighting and to develop architectural and lighting projects that value the lighting in work spaces, with differentiated and creative proposals allowing for different lighting solutions in order to improve the quality of work spaces, where the absence or excess of light causes discomfort and influences productivity. The ABNT NBR 8995-1 - lighting in work environments and the Occupational Hygiene (NHO 11) will be used as a reference to analyze the requirements to be considered to develop a good lighting project. In addition, the enhancement of lighting can contribute to work spaces with differentiated and creative architectural projects, allowing for different solutions. Lighting is always present in everyday life, whether through natural or artificial lighting, electricity or alternative sources, and the purpose of adequate lighting is to help with visual efficiency and the correct use of lighting provides several benefits to the user, such as visual safety at the time the development of activities and comfort. The effects that artificial lighting causes are direct, indirect or diffuse and there are several factors that must be taken into account regarding the proper use of lighting and lack of knowledge can cause a series of problems such as: headache, fatigue, discomfort , among others. Good lighting in the work environment provides better productivity, increasing users’ willingness, quality of life and health, reducing the risk of possible accidents or errors. The research complements with Case Studies, highlighting the benefits of a good project and the correct use of natural and artificial lighting in the work environment, as well as addressing possible alternatives that the advancement of technology makes possible, such as the use of automation in the work environment.